Enhancing Older Adults’ Mental Health Through Tailored Innovative Educational Interventions in Community - Indra Ruswadi; Masliha Masliha; Nafisah Itsna Hasni; Jummai Wennie (Yayasan Keluarga Guru Mandiri, 2025)
Mental health problems, including depression, anxiety, and feelings of social isolation, frequently occur in older adults and often go unaddressed in community environments. This research aimed to assess the impact of an educational initiative delivered at the community level on enhancing the psychological well-being of older adults. A pre-experimental approach was utilized, employing a single-group design with measurements taken before and after the intervention. The program emphasized mental health awareness, emotional self-regulation techniques, and involvement in socially engaging community events. The analysis demonstrated notable enhancements in mental well-being. Participants experienced a reduction in depression from moderate to mild levels, decreased anxiety symptoms, and a marked improvement in their sense of social belonging, rising from low to moderate to high engagement. These outcomes demonstrate that a structured and targeted educational strategy can lead to significant improvements in the mental health of older adults. The intervention proved to be both feasible and beneficial in addressing psychological challenges in later life. Furthermore, the study offers valuable insights for public and geriatric mental health practices by presenting adaptable, evidence-driven approaches to promote healthy aging.